Dampak Penambahan Lamtoro (Leucaena leucocephala) pada Pakan Terhadap Status Fisiologis Ternak Kambing Kacang (Capra aegragus hircus): Impact of Additional Lamtoro (Leucaena leucocephala) to the Feed On The Physiological Status Of kambing kacang (Capra aegragus hircus) - John Arnold Palulungan; Evi Warintan Saragih; Purwaningsih; Noviyanti Noviyanti (Fakultas Peternakan Universitas Papua, 2022)
Abstrak This study aims to determine the impact of the physiological status of goats with a higher proportion of lamtoro leaves. Forage feed given to goats consisted of a combination of raja grass, Gamal and lamtoro leaves with the following composition: P1= Raja grass 50% + Gamal 50%; P2= Raja grass 40% + Gamal leaf 40% + Lamtoro leaf 20%; P3 = Raja grass 30% + Gamal leaf 30% + Lamtoro leaf 40%. In general, the provision of lamtoro leaves up to 40% of the total ratio did not have a negative impact on the kambing kacang growth and health. The rectal temperature and pulse count in goats were in the normal range for goats, but the respiration rate was twice the normal range. The high frequency of respiration is thought to be due to the high proportion of legumes in the ratio which can increase the amount of feed consumption due to the high palatability of the legumes. This will have an impact on the body's metabolism which is indicated by an increase in respiration. However, the high frequency of respiration in this study can also be caused by environmental factors (temperature and humidty) which were quite high during the study. Keywords: Capra aegragus hircus; Goat; Leucaena leucocephala; Physiologis status. Abstract Penelitian ini bertujuan untuk mengetahui dampak pemberian lamtoro (Leucaena leucocephala) pada status fisiologi ternak kambing kacang. Proporsi daun lamtoro pada pakan ternak kambing diberikan berkisar antara 20-40%. Pemberian lamtoro dikombinasikan dengan pakan hijauan lain dengan komposisi sebagai berikut: P1= Rumput raja 50 % + gamal 50% + lamtor (0%); P2= Rumput raja 40% +daun gamal 40% + daun lamtoro 20%; P3= Rumput raja 30% + daun gamal 30% + daun lamtoro 40%. Secara umum pemberian daun lamtoro hingga 40% dari total ransum tidak memberikan dampak negatif terhadap status fisiologi ternak kambing kacang. Suhu rektal dan jumlah pulsus pada ternak kambing berada pada kisaran normal untuk ternak kambing, namun jumlah respirasi dua kali lipat dari kisaran normal. Tingginya frekwensi respirasi diuga disebagakan tingginya proporsi legum pada ransum yang dapat meningkatkan jumlah konsumsi pakan karena tingginya palatabilitas legum. Hal ini akan berdampak pada metabolisme tubuh yang diindikasikan dengan peningkatan respirasi. Namun demikian tingginya frekwensi respirasi pada penelitian ini dapat juga disebabkan faktor lingkungan (temperature dan kelembaban) yang cukup tinggi semasa penelitian. Kata kunci: Capra aegragus hircus; Kambing kacang; Leucaena leucocephala; Status fisiologis